Perceptions surrounding Madikwe Game Reserve’s current management: implications for sustainability and future climate change responses - Galvao, Amy (My University, 2022)
Ecotourism Based Protected Areas (ETBPAs) are becoming more vulnerable to climate change impacts, hindering their ability to safeguard ecosystems and ecotourism products. A bottom-up understanding of ETBPA’s social-ecological systems could potentially provide climate change impact management solutions. Using a case study approach, this study gains a bottom-up understanding of Madikwe Game Reserve’s (MGR) social-ecological system through the perceptions of 31 onsite community members (OSCMs) through semi-structured interviews. These perceptions focus on MGR’s current management and the implications for MGR’s, and similar ETBPA’s, sustainability, both currently and in the face of future climate change. Findings indicate governance inefficiency, ecotourism-focused management priorities, and scientific knowledge gaps have caused major implications for MGR’s ecological sustainability, mainly through the cascading impacts of an elephant overpopulation. These management issues also limit MGR’s ability to respond to climate change impacts both currently and in the future.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand,Johannesburg, 2022